FRI0220 Prescription of Tocilizumab Alone or in Combination with Dmards in Rheumatoid Arthritis Patients in A Real Life Setting: The Act-Solo Study 12 Months Results. (15th July 2016) - Tebib, J.; Idier, I.; Coudert, M.; Maillefert, J.-F.; Flipo, R.-M.
Abstract : Background: Although the use of a biologic as monotherapy is not the standard in Rheumatoid Arthritis (RA), it concerns around a third of the patients. The objectives of the Act Solo study was to evaluate tocilizumab (TCZ) alone (Mono) or in combination (Combo) at 12 months in real life. Methods: Prospective, multicenter, longitudinal, non-interventional 12-month study in RA pts requiring TCZ according to their physician. Besides drug retention rate, efficacy and safety, the effect of Mono when compared to Combo was evaluated using a propensity score. Efficacy population was pts fulfilling inclusion and non-inclusion criteria and with ≥1 TCZ infusion. Safety population was all pts with ≥1 TCZ infusion. Results: 608 pts were recruited of whom 603 were analysed for safety and 577 (Total) for other endpoints. At baseline: mean age 57±13 years, 454 (79%) females, at least 1 co-morbidity: 409 (71%), mean RA duration 11±9 years, RF or ACPA positive: 478 (86%), erosive disease: 435 (77%), mean DAS28 5.2±1.3. Past RA treatments included DMARDs + biologics in 75%, only DMARDs in 24%. MTX was previously prescribed in 95% of pts and in 71% within the last 2 years. TCZ Mono was initiated in 228 (40%) pts and TCZ Combo in 349 (60%) pts of whom 80% received MTX (mean 16±5mg/w). Steroids (GCs) were used in 386 (67%) pts (mean 10±7mg/d). 337 pts completed M12 visit. 194 pts withdrew for: AE 53 pts, inefficacy 88, patients wish 12, lost to follow-up 23, other 18. At M12, drug retention rate was 69% in Total, 67% in Mono, 71% in Combo (Fig. ). Mean number of TCZ infusions was 9.4±4.1; mean time between infusions was 31.8 ±12.6 days. 29% of the pts experienced at least 1 discontinuation, 25% and 33% in Mono and Combo groups respectively. DMARD was added in 20 Mono and definitely stopped in 25 Combo pts. 170 (50%) pts remained on GCs, 66 (51%) in Mono group and 104 (50%) in Combo group. At M12, mean DAS28 in Total, Mono and Combo were 2.4±1.3, 2.4±1.3 and 2.3±1.2 respectively. DAS28 remission was 35% in Total, 35% and 36% in Mono and Combo respectively (p=0.83). Using the propensity score, no effect of Mono was observed on drug retention HR=1.194 [0.852, 1.673], p=0.30; DAS remission OR=1.111 [0.773, 1.597], p=0.57; or GCs use OR=0.880 [0.558, 1.387], p=0.58 at M12. No new safety signal was reported. 325 (54%) patients had at least one AE, 74 (12%) had at least one serious AE with no differences between Mono and Combo. Conclusions: The Act Solo study confirms, in real life, the clinical results of RCTs showing a comparable efficacy of TCZ as monotherapy when compared to combotherapy. No new safety signal occurred. Disclosure of Interest: J. Tebib: None declared, I. Idier Employee of: Chugai Pharma France, M. Coudert: None declared, J.-F. Maillefert: None declared, R.-M. Flipo Consultant for: Roche SAS and Chugai Pharma France